Intraluminal duodenal ("Windsock") diverticulum: a rare cause of gastrointestinal bleeding - Eusébio, Marta (2016)
Intraluminal duodenal diverticulum (IDD), also known as ‘‘windsock’’ diverticulum, is a rare congenital abnormality that seems to result from an incomplete recanalization of the foregut lumen. Symptoms usually do not appear until the third decade of life (...).